Crp Induces Switching of the CsrB and CsrC RNAs in Yersinia pseudotuberculosis and Links Nutritional Status to Virulence - Heroven, AnnKathrin; Sest, Maike; Pisano, Fabio; Scheb-Wetzel, Matthias; Böhme, Katja; Klein, Johannes; Münch, Richard; Schomburg, Dietmar; Dersch, Petra (Frontiers in Cellular and Infection Microbiology, 2012)
Colonization of the intestinal tract and dissemination into deeper tissues by the enteric pathogen Yersinia pseudotuberculosis demands expression of a special set of virulence factors important for the initiation and the persistence of the infection. In this study we demonstrate that many virulence-associated functions are coregulated with the carbohydrate metabolism. This link is mediated by the carbon storage regulator (Csr) system, including the regulatory RNAs CsrB and CsrC, and the cAMP receptor protein (Crp), which both control virulence gene expression in response to the nutrient composition of the medium. Here, we show that Crp regulates the synthesis of both Csr RNAs in an opposite manner. A loss of the crp gene resulted in a strong upregulation of CsrB synthesis, whereas CsrC levels were strongly reduced leading to downregulation of the virulence regulator RovA. Switching of the Csr RNA involves Crp-mediated repression of the response regulator UvrY which activates csrB transcription. To elucidate the regulatory links between virulence and carbon metabolism, we performed comparative metabolome, transcriptome and phenotypic microarray analyses and found that Crp promotes oxidative catabolism of many different carbon sources, whereas fermentative patterns of metabolism are favoured when crp is deleted. Mouse infection experiments further demonstrated that Crp is pivotal for a successful Y. pseudotuberculosis infection. In summary, placement of the Csr system and important virulence factors under control of Crp enables this pathogen to link its nutritional status to virulence in order to optimize biological fitness and infection efficiency through the infectious life cycle.